The neural bases of the multiplication problem-size effect across countries - Prado, Jérôme; Lu, Jiayan; Liu, Li; Dong, Qi; Zhou, Xinlin; Booth, James R. (Frontiers in Human Neuroscience, 2013)
Multiplication problems involving large numbers (e.g., 9x8) are more difficult to solve than problems involving small numbers (e.g., 2x3). Behavioral research indicates that this problem-size effect might be due to different factors across countries and educational systems. However, there is no neuroimaging evidence supporting this hypothesis. Here, we compared the neural correlates of the multiplication problem-size effect in adults educated in China and the United States. We found a greater neural problem-size effect in Chinese than American participants in bilateral superior temporal regions associated with phonological processing. However, we found a greater neural problem-size effect in American than Chinese participants in right intra-parietal sulcus associated with calculation procedures. Therefore, while the multiplication problem-size effect might be a verbal retrieval effect in Chinese as compared to American participants, it may instead stem from the use of calculation procedures in American as compared to Chinese participants. Our results indicate that differences in educational practices might affect the neural bases of symbolic arithmetic.